PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI PEDESAAN Telaahan atas tulisan David C. Korten - Badrun Susantyo (Politeknik Kesejahteraan Sosial, 2007)
Participation is like a small coin, one side to assume the shape of participation with theirwhole and the other side to show the spirit of participation. Community participation are adevelop paradigm to focusing the involved of community, beginning from planning. Communityparticipation has an opportunity to influence the policy of development, to answered what thepeople needed. Through the participation, people knowing their problem and how to solved.Besides it, they have resources to improved their live good.Key words : Participation, local community, rural development.